AUTHORITY OF NURSES TO INSTALL INFUSATIONS DURING THE PANDEMIC OUTSIDE OF HEALTH CARE FACILITIES - Effendi, Prihatin; Nasichim , Mohammad (IBLAM LAW REVIEW, 2024)
During the COVID-19 pandemic emergency, one of the medical measures that nurses can use in certain limited conditions is installing infusion outside of healthcare institutions. The author's study methodology, which employs three approaches—legislation (statement approach), comparative approach (comparative approach), and conceptual approach (conceptual approach)—uses a normative legal research type to address these issues. Furthermore, primary, secondary, and tertiary legal documents are the sources of the legal materials used. The study's findings clarify the role and authority of nurses for infusions outside of healthcare facilities during the pandemic. Specifically, a nurse who is ill or in a state of restricted mobility during the COVID-19 emergency period is authorised to administer first aid in the form of medical action, such as infusions, in accordance with the law and her expertise in assessing the patient's condition. Although the nurse is personally accountable for the infusion because it is an autonomous duty, meaning that the nurse in question will take full responsibility if a mistake is made.